Parametric sensitivity analysis of the separation process for n-butanol production - Z. J., Johan; T. Z., Tuan Muda; Chin, Sim Yee (IOP Publishing Ltd, 2020)
n-butanol and iso-butanol are commonly produced by the hydrogenation of n-butyraldehyde and iso-butyraldehyde employing the patented copper catalyst accommodated in the reactors in series. The main cause of the lower n-butanol and iso-butanol yield was due to the catalyst blockage rendering a pressure build-up that could lead to a plant shut down. Bypassing the last reactor from the series could be a potential solution to continue running the plant until the next shutdown plan to replace catalyst. The study adopted simulation approach using Aspen Plus V10 to investigate the effect of bypassing the last reactor in the series to the product purity of the downstream separation processes. The iso-butanol and n-butanol with the desired purity were produced from the distillate and bottom product when the column was operated at the RR of 8.03 and DF of 0.328. The reaction conversion of R-102 was varied from 0.1-0.995 but the variation did not significantly change the composition of the main product. Hence, the present study affirmed that the bypassing of third reactor from the reactor train would not affect the product purity of the main product, n-butanol.